(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the historical and pedagogical foundations of Uzbek folk applied art and the “master-apprentice” system. It examines the heritage of Eastern thinkers, the experience of regional master schools, and the issues of integrating national craftsmanship traditions into modern education. The research results substantiate that the master-apprentice system is a holistic pedagogical model that harmoniously develops professional skills, moral ethics, and creative thinking in an apprentice.